2015
DOI: 10.1016/j.bbamem.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of action of different concentrations of ethanol in water on ordered structures of intercellular lipids and soft keratin in the stratum corneum

Abstract: Ethanol (EtOH) is one of the bases in topically applied medicines that promote the skin permeation of drugs. Although the effects of EtOH have been attributed to structural modifications in the stratum corneum, the underlying mechanisms, especially the influence of different concentrations of EtOH, have not been examined extensively. Structural modifications in the stratum corneum of hairless mouse due to the application of EtOH/water mixture were herein investigated at the molecular level using synchrotron X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 25 publications
1
30
0
2
Order By: Relevance
“…34,35) However, the interactions of these CPEs with SC lipids was mainly on the polar head region. 34,36,37) Therefore, low fluidity in the hydrophobic chain of SCLL lipids was observed in our study.…”
Section: Discussionmentioning
confidence: 83%
“…34,35) However, the interactions of these CPEs with SC lipids was mainly on the polar head region. 34,36,37) Therefore, low fluidity in the hydrophobic chain of SCLL lipids was observed in our study.…”
Section: Discussionmentioning
confidence: 83%
“…Moghadem et al [21] reported that ethanol produces very little change in the small-and wide-angle diffraction patterns of SC lipids. However, examining hairless mouse skin, Horita et al [22] reported that ethanol modified the short but not the long periodicity phase of SC lipids. Changes to keratin structure have also been reported with increasing concentrations of ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The results revealed that ethanol modifies both the short lamellar structures, including the aqueous layer in intercellular lipids, and the structure of keratin fibrils in corneocytes, which can penetrate hydrophilic compounds such as caffeine.…”
Section: Resultsmentioning
confidence: 99%
“…In ceramide, fatty acids are linked with sphingosine back bone, and a 2-amino, 1, 3-diol head of sphingosine can hinder any substance with a hydrophilic residue from penetrating the skin by means of hydrogen bonding. [9] TA might disrupt the hydrogen bond between caffeine and ceramide, and consequently, percutaneous caffeine absorption could be significantly increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation